The Role Of Csr Disclosure And Sustainability Reporting In Enhancing Stakeholder Satisfaction: A Systematic Literature Review Of The Coal Subsector - Maria Dinda Sabrina; Azizul Kholis; Jufri Darma (JURNAL ECONOMINA, 2026)
This study uses the Systematic Literature Review (SLR) method to investigate the relationship between CSR and Sustainability Reporting disclosure and stakeholder satisfaction in coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX). 36 indexed from 2015 to 2024 were related to the topics of CSR, SR, and stakeholder satisfaction. The results show that transparency, compliance with global standards, and stakeholder engagement increase as a result effective CSR and SR disclosure. This enhances legitimacy and stakeholder satisfaction. Symbolic reporting, on the other hand, has little impact and even reduces public trust. The results confirm that high-quality non-financial disclosure is an important component of corporate communication and accountability strategies. The results confirm that good non-financial disclosure is an important component of corporate communication and accountability strategies. This study confirms that stakeholder theory and legitimacy are crucial for explaining how sustainability reporting contributes to corporate social relations and why the extractive industry needs better reporting.